1980
DOI: 10.1104/pp.66.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein Phosphatase of Soybean Hypocotyls

Abstract: A soybean histone-type protein kinase was used to prepare 32P-labeled histone Hi as substrate for purification and characterization of a phosphoprotein phosphatase (EC 3.13.16) phorylation and dephosphorylation has been suggested to be an important mechanism in the control of metabolic processes in higher plants (12,25). Randall and his colleagues (21) have shown that phosphorylation of the pyruvate dehydrogenase complex from broccoli mitochondria results in inactivation of the enzyme. Additionally, the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…Protein phosphatase 1 related enzymes have been detected in all eukaryotic cells tested. Thus, it was not unexpected that protein phosphatases would be detected in higher plants (Bennett, 1980;Lin et al, 1980;Polya and Haritou, 1988; MacKintosh and Cohen, 1989). It was found that of the four major protein phosphatase catalytic subunits, only type 1 and type 2A activities were present in plant cell extracts at particularly high levels (MacKintosh and Cohen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase 1 related enzymes have been detected in all eukaryotic cells tested. Thus, it was not unexpected that protein phosphatases would be detected in higher plants (Bennett, 1980;Lin et al, 1980;Polya and Haritou, 1988; MacKintosh and Cohen, 1989). It was found that of the four major protein phosphatase catalytic subunits, only type 1 and type 2A activities were present in plant cell extracts at particularly high levels (MacKintosh and Cohen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…These genes can be grouped into three families: the family consisting of PP2A-1, PP2A-2 and the gene product containing the AP-1 sequence, all of them very related to each other and also to the PP2A proteins from other organisms; the family that includes PP2A-3, also very related to other PP2A proteins (Table 1); and the family corresponding to the gene(s) containing the AP-2 sequence, more distantly related to the previously mentioned families and also to the type 2A phosphatases from other organisms, but still closer to the type 2A family than to type 1 or 2B phosphatases. Whether or not any of these proteins correspond to plant phosphatase activities so far characterized [14,19,26] cannot be determined at present. It fact, it would be very interesting to know if the complexity of type 2A protein phosphatase gene family found in A.…”
Section: Identification In a Thaliana Of Six Different Genes Encodinmentioning
confidence: 99%
“…Under the conditions studied, the Tp fraction lacks any protein phosphatase activity. In this fraction, the cycle of phosphorylation and dephosphorylation may be completed by a soluble protein phosphatase (14) …”
Section: Resultsmentioning
confidence: 99%
“…When labeling by protein kinase was stopped by adding 5 mM ATP, no phosphatase activity was detected in either fraction. This observation suggests that ATP may serve as a substrate for the protein phosphatase and competes with phosphoprotein as a substrate (14). Endogenous membrane protein phosphatase (8,23) and soluble phospho-histone H 1 phosphatase (14) have been reported in plants.…”
Section: Protein Phosphatasementioning
confidence: 99%